Optimal design for improving torque performance of permanent magnet motor - Kyoung Bang, Tae; Hun Shin, Kyung; In Lee, Jeong; Han, Cheol; Kook Cho, Sung; Wook Cho, Han; Young Choi, Jang (International Journal of Engineering and Technology, 2018)
Background/Objectives: This paper deals with the optimal design of the BLDC motor considering a rotor structure that is used to electrically drive tools. Generally, electrically driven tools employ the BLDC motor, which should be able to operate in high-speed and high-vibration environments. However, it has the disadvantages of a high torque ripple and significant waveform fluctuation. Therefore, it is necessary to optimize it according to the usage condition.Methods/Statistical analysis: In improving the torque performance, this study performed the optimization process by employing the Taguchi method, which can achieve a robust design based on the design variables. In the optimization process, the objective functions are set using a weighting ratio depending on the importance of the objective function as back EMF, torque performance, and loss. Through the optimization process, the optimal design point that improved the performance of the objective function is derived. The improved design that applied the optimal design point is compared with the original design by using the finite element method (FEM) analysis results.Findings: In this study, the optimum design of the motor according to the design variables and the objective function is derived through the optimum design method using the Taguchi method by adopting the motor for the electrically driven tool as the interior permanent magnet type BLDC motor and the FEM results. Moreover, by comparing the analysis results with the optimized model and the initial model, the optimum design point that satisfies the restriction specification and the rated specification was found.Improvements/Applications: The optimum design point was found by using the Taguchi method and the loss and torque characteristics were improved.Â